2002
DOI: 10.1046/j.1365-2958.2002.03152.x
|View full text |Cite
|
Sign up to set email alerts
|

The functions of OmpATb, a pore‐forming protein of Mycobacterium tuberculosis

Abstract: SummaryThe functions of OmpATb, the product of the ompATb gene of Mycobacterium tuberculosis and a putative porin, were investigated by studying a mutant with a targeted deletion of the gene, and by observing expression of the gene in wild-type M. tuberculosis H37Rv by real-time polymerase chain reaction (PCR) and immunoblotting. The loss of ompATb had no effect on growth under normal conditions, but caused a major reduction in ability to grow at reduced pH. The gene was substantially upregulated in wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 57 publications
7
108
2
Order By: Relevance
“…In contrast to our findings, other studies have demonstrated that mycobacterial gene deletion mutants generally have reduced pathogenicity and/or ability to replicate in macrophages. For example, deletion of the ompATb gene of M. tuberculosis, a gene coding for a putative porin, leads to reduced intracellular replication in macrophages, possibly as a result of diminished ability to respond to reduced phagosomal pH (Raynaud et al, 2002). In addition, using a genetic approach, we confirm the results of our prior study, which was the first to provide evidence that a cell-wall lipid (GPL) can mask underlying immunostimulatory cell-wall lipids (Rhoades et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to our findings, other studies have demonstrated that mycobacterial gene deletion mutants generally have reduced pathogenicity and/or ability to replicate in macrophages. For example, deletion of the ompATb gene of M. tuberculosis, a gene coding for a putative porin, leads to reduced intracellular replication in macrophages, possibly as a result of diminished ability to respond to reduced phagosomal pH (Raynaud et al, 2002). In addition, using a genetic approach, we confirm the results of our prior study, which was the first to provide evidence that a cell-wall lipid (GPL) can mask underlying immunostimulatory cell-wall lipids (Rhoades et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Although the low permeability of OmpA-like porins (see "Slow porins" above) is attractive in explaining the generally low permeability of the mycobacterial cell wall, it is rather difficult to imagine that a protein similar to those that traverse the thickness of E. coli OM could span the much thicker mycobacterial cell wall. A deletion mutant containing a mutation of this gene was constructed recently (535). It had difficulty in growing in acidic media, and at pH 5.5 the uptake of serine was nearly totally abolished in the mutant, suggesting that this protein is a major porin under these conditions.…”
Section: Other Porinsmentioning
confidence: 99%
“…Despite the well-documented importance of OMPs for the import of nutrients, secretion processes and host-pathogen interactions in gram-negative bacteria 10 , surprisingly few OMPs of mycobacteria are known. The only two well characterized examples of integral OMPs are the porin MspA of M. smegmatis and the channelforming protein OmpA of M. tuberculosis [11][12][13][14] . By contrast, E. coli uses more than 60 proteins to functionalize its outer membrane 15 , none of which has significant sequence similarity to any M. tuberculosis protein.…”
Section: Introductionmentioning
confidence: 99%